Odpowiedzi

2010-01-02T05:27:15+01:00
(2x-8 / x²-8x) - (3x-16 / 2x² -32) =

i teraz duuuuża kreska ułamkowa:

(2x-8)(2x² -32) - (3x-16)(x²-8x)
____________________________ =
(x²-8x)(2x² -32)

(4x³ - 64x - 16x² + 256) - (3x³ - 24x² - 16x² + 128)
___________________________________________ =
2x⁴- 32x² - 16x³ + 256x

4x³ - 64x - 16x² + 256 - 3x³ + 24x² + 16x² - 128
___________________________________________ =
2x(x³ - 8x² - 16x + 128)

x³ + 24x² - 64x + 128
____________________ =
2x(x³ - 8(x² - 2x + 16))

nijak mi tu ten wynik nie wychodzi.